User Tools

Site Tools


journal:fall2019:jgleas15:week12

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
Next revision
Previous revision
journal:fall2019:jgleas15:week12 [2019/11/08 13:21]
jgleas15
journal:fall2019:jgleas15:week12 [2019/11/11 15:59] (current)
jgleas15
Line 20: Line 20:
  
  
 +First thing we can see clearly right away is that E must = 0 For example we see D - E = D where D cannot be borrowing so E must = 0 for this to be true
  
 +Next we can find the value of C if we take a look at C - E = E since we know that E = 0 and C cannot = E so C must be being borrowed from meaning C would = 1
 +
 +Next we can look at the bottom at E - Z = Z which is next to G - G = E so E must be borrowing but not being borrowed from so it is really (E + 10) - Z = Z so the only value that would work for Z would be for Z to = 6
 +
 +Now we can look at the middle at G - C = Z which is next to E - E = E so G is not borrowing or being borrowed from so the equation is G - 1 = 6 so G = 7
 +
 +Next we can narrow down some values, so now taking a look at the bottom we see Q - G = S which is next to G - G = E so Q is not borrowing meaning S << Q and G << Q now we can look at G - M = Q and since G << Q then G must be borrowing meaning G << M
 +
 +Next we will look at D - O = G where we know that D in not borrowing but D is being borrowed from so we know that D is >> G and since O has to be greater than 1 since we found the values of 1 and 0 and D is being borrowed from so D is at east 3 more than G which = 7 so D is either A or B in base 12 while O = 2 or 3
 +
 +Now we will look at Z - S = C where Z is being borrowed from but not borrowing so the equation is really (6 - 1) - S = 1 so S = 4
 +
 +Next we will look at Q - G = S which is not being borrowed from or borrowing so the equation is Q - 7 = 4 so Q = B meaning D = A and O = 2
 +
 +Now we can look at D - J = C where there is no borrowing taking place so the equation in base 12 is A - J = 1 so J = 9 and since M >> G, the only value left for M to = is 8
 +
 +Finally we can look at T - I = C where T is being borrowed from so the equation is (T - 1) - I = 1 or T - I = 2 and since 5 and 3 are the only values left T = 5 and I = 3
 +
 +so we have 
 +
 +0 = E
 +
 +1 = C
 +
 +2 = O
 +
 +3 = I
 +
 +4 = S
 +
 +5 = T
 +
 +6 = Z
 +
 +7 = G
 +
 +8 = M
 +
 +9 = J
 +
 +A = D
 +
 +B = Q
 +
 +For verification we put the values back in to the puzzle and solve in base 12
 +
 +
 +                 285
 +           ​_________
 +   ​1A6164 | 50AA167B
 +           ​-390308
 +            ======
 +            13A70A7
 +           ​-1301028
 +            =======
 +              A607BB
 +             ​-946778
 +              ======
 +              116043
 +
 +Through plugging in the values for verification the values match
  
  
  
journal/fall2019/jgleas15/week12.1573237317.txt.gz · Last modified: 2019/11/08 13:21 by jgleas15